2015
DOI: 10.1111/eci.12465
|View full text |Cite
|
Sign up to set email alerts
|

The diagnosis and management of inpatient hyponatraemia and SIADH

Abstract: BackgroundHyponatraemia is a very common medical condition that is associated with multiple poor clinical outcomes and is often managed suboptimally because of inadequate assessment and investigation. Previously published guidelines for its management are often complex and impractical to follow in a hospital environment, where patients may present to divergent specialists, as well as to generalists.DesignA group of senior, experienced UK clinicians, met to develop a practical algorithm for the assessment and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
71
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 25 publications
0
71
0
1
Order By: Relevance
“…Grant et al recently published algorithm for inpatient management of hyponatremia [16]. Symptomatic hyponatremia requires immediate hypertonic saline (3%).…”
Section: Discussionmentioning
confidence: 99%
“…Grant et al recently published algorithm for inpatient management of hyponatremia [16]. Symptomatic hyponatremia requires immediate hypertonic saline (3%).…”
Section: Discussionmentioning
confidence: 99%
“…More studies are required to address the potential safety concerns of chronic use, because tolvaptan, a V2-receptor antagonist, is an excellent choice, especially in patients with lung malignancies (Grohe et al 2015, Thajudeen et al 2016). It has recently been shown that prompt endocrine input improved time for the correction of hyponatraemia and shortened length of hospitalisation, and the widespread provision of endocrine input should be considered (Verbalis et al 2014, Grant et al 2015, Tzoulis et al 2016). …”
Section: Syndrome Of Inappropriate Anti-diuretic Hormone Secretion (Smentioning
confidence: 99%
“…It is important nurses administering hypertonic saline are aware of these side effects especially to observe for hypernatraemia, as rapid changes in serum sodium can have detrimental and permanent neurological effects on the patient. Hence, serum sodium should not rise more than 10mmol/L within 24 hours and 18mmol/L within 48 hours to prevent osmotic demyelination syndrome (Ball & Iqbal, 2015;Grant et al, 2015;Rafat et al, 2014;Sood, Sterns, Hix, Silver, & Chen, 2013). Osmotic demyelination syndrome typically occurs 2-7 days post treatment and is clinically characterised by irreversible neurological damage (Sood et al, 2013).…”
Section: Hypertonic Salinementioning
confidence: 99%